Beyond Anxiety: A Mixed-Methods Needs Analysis of Postgraduate ELT Students in a Quantitative Research Methodology Course - Nur, Sahril; Abdullah; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
As evidence-based practice in English Language Teaching (ELT) grows, postgraduate students' quantitative research proficiency is critical. However, students from humanities backgrounds often exhibit significant apprehension. This mixed-methods study conducted a needs analysis to explore the self-efficacy, attitudes, and learning needs of 30 incoming Master's students in an Indonesian ELT program before a mandatory quantitative methodology course. Data were collected via a questionnaire with quantitative scales and qualitative open-ended questions. Findings reveal a paradox: students perceive quantitative skills as highly useful for their careers (M=4.57) but report high anxiety (M=4.10) and low self-efficacy in statistical tasks (M=2.13). Qualitative themes indicate that anxiety is rooted in past experiences and exacerbated by a reluctance to seek help. Motivation is highly instrumental, focused on thesis completion. The study concludes that this cohort is pragmatically motivated but emotionally and technically underprepared, necessitating a pedagogy that explicitly addresses anxiety and builds practical, thesis-relevant skills.